Multiteam systems as integrated networks for engaging ambidexterity as dynamic capabilities. Issue 4 (29th September 2021) - Dean, Benjamin P.
Abstract : Purpose: This inquiry aims to determine the features and mechanisms that specially enable a multiteam system (MTS) to develop ambidexterity that can deal effectively with rapid changes in dynamic environments. The MTS is an emerging organizational unit comprised of tightly integrated networks of teams that may originate from one or more firms. The inquiry also considered how an MTS can engage those features and mechanisms to maximize ambidexterity as dynamic capabilities for increased innovation and long-term adaptation under complex, volatile conditions. Design/methodology/approach: This conceptual inquiry integrates the emerging research on MTSs with theory and studies relating to ambidexterity and dynamic capabilities. This inquiry focuses on the attributes and linkages that specially characterize an MTS. It analyzes these to determine the key mechanisms and interactions enabling and engaging ambidexterity at MTS unit level. Findings: MTSs can engage powerful mechanisms for ambidexterity functioning as dynamic capabilities at meso-organizational level. The attributes and linkages that distinguish an MTS from other units enable it to deal effectively and efficiently with near-term task demands by simultaneously balancing the essential tasks of exploration and exploitation, and by being able to rapidly adapt by reconfiguring taskwork and reallocating resources as required for sustainable innovation and long-term success within a dynamic environment. Practical implications: This inquiry provides valuable insights for designing MTSs that are equipped with selected teams, flexible memberships, specialized skills and permeable interfaces. Autonomy for an MTS allows the unit to span internal and external organizational boundaries to gain access to new discoveries and to exchange information and material resources for increased innovation. Ambidexterity as dynamic capabilities facilitates exploitation of current resources by efficiently reconfiguring taskwork and reallocating materials for adaptation and competitive advantage. Originality/value: This inquiry appears to represent the most integrative effort to examine the underexplored potential of MTSs for developing and engaging ambidexterity functioning as dynamic capabilities. The inquiry appears to be a first effort at articulating a concept of MTS ambidexterity distinct from organizational ambidexterity. The analysis synthesizes a systems model that guides organizational leaders and opens new opportunities for future research.